2018
DOI: 10.1021/jacs.8b10212
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Herquline B and C

Abstract: The total syntheses of (−)-herquline B (2) and a heretofore-unrecognized congener, (+)-herquline C (3), are described. The syntheses require 14 and 13 steps, respectively, and feature a key oxazoline reduction that sets the stage for piperazine construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 12 publications
(12 reference statements)
0
30
0
Order By: Relevance
“…We are grateful to Professor John L. Wood for sharing a copy of ref 9 prior to publication. Financial support for this work was provided by NIH (GM-118176).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are grateful to Professor John L. Wood for sharing a copy of ref 9 prior to publication. Financial support for this work was provided by NIH (GM-118176).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A landmark study by the Tang group 8 recently revealed its unusual reductive biosynthesis, while the Wood group demystified the stereochemistry of 3 in their elegant synthesis. 9 The difficulty of assembling such structures is well documented and is described in detail below. This Communication outlines a concise entry into the herquline family that strategically mirrors the biosynthesis by employing a carefully choreographed sequence of chemical reductions from a simple tyrosine-based starting material.…”
mentioning
confidence: 99%
“…In 2015, Yang and Simpkins described their efforts towards the herqulines (Scheme 2, F). 8 Prior to them undertaking their studies, the total synthesis of mycocyclosin (4) had been reported, and this informed their strategy significantly. Beginning with a biomimetic approach, multiple piperazine substrates 29 were evaluated under intramolecular oxidative phenolic coupling conditions, but without success.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…The absolute configuration at C3-C3′ was not determined until the total synthesis efforts in 2019 by Wood and co-workers (see Section 5). 4 Finally, in addition to herqulines A (1) and B (2), a third congener, herquline C (3), was isolated by Tang and co-workers during the course of their investigations Corinna S. Schindler received her diploma in chemistry from the Technical University of Munich in Germany. After a research stay with Prof. K. C. Nicolaou at the Scripps Research Institute in La Jolla (USA), she joined the group of Prof. Erick M. Carreira at ETH Zurich in Switzerland for her graduate studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation